THE ROLE OF PSYCHOLOGICAL CHARACTERISTICS IN THE DEVELOPMENT OF COMMUNICATION STYLE IN A TALENTED PERSON - Abdullayeva , Zuhro Ismailovna (Educational Research in Universal Sciences, 2023)
In this article, the role of talent and culture of communication is the most necessary factor for a person in the development of a person’s communication style. The main reason why a person is called a product of social relations means that he is always in the circle of people, in the framework of interaction with them. This indicates that one of the most leading and influential activities of a person is communication. It is an important task for teachers and psychologists to identify gifted children in time, to direct their talents to a specific field.